Evaluation of Architectural Institute of Japan (AIJ) habitability criteria using local site conditions - Dimapilis, Marc Jill M.
One reference in assessing occupant comfort is the AIJ Guidelines for Evaluating Habitability due to Building Vibration 2004 (AIJ GBV 2004). It relates acceleration, frequency and vibration perception. However, given that this concept has not yet been included in our structural code, the goal of this research is to evaluate the AIJ GBV 2004 using local site conditions. Using four test buildings, its code-derived (NSCP 2015 and AIJ RLB 2004) and experimental (vibration measure test) acceleration and frequency values were determined. Experimental results showed that the acceleration values were low enough such that it wouldn't cause disturbing effects on the occupants during ambient conditions. In comparison with using code estimates, both codes have largely underestimated the acceleration values. To assess the AIJ Habitability curve, code-derived acceleration values using PSWS #1 conditions (60 kph) were utilized to simulate high wind speed condition. Results showed that even at this condition, no perceptible vibrations will occur. However, this is contrary to the results of the occupant survey. For Tower D, 10% (5 out of 50) of the respondents perceived motion. Since the applicability of the AIJ Habitability Curve can only be evaluated based on its input parameters, the researcher argues that this contradicting result is because of the gross underestimation in acceleration values of code equations. Thus, on the basis of the four case buildings, it cannot be effectively used in designing structures on occupant comfort limit state until a more suitable acceleration estimation method is developed. In assessment of constructed buildings, peak acceleration must be obtained using field vibration test under typhoon conditions.